Inhibition of vaccinia virus L1 N-myristoylation by the host N-myristoyltransferase inhibitor IMP-1088 generates non-infectious virions defective in cell entry - Priyamvada,L; Kallemeijn,WW; Faronato,M; Wilkins,K; Goldsmith,CS; Cotter,CA; Ojeda,S; Solari,R; Moss,B; Tate,EW; Satheshkumar,PS (PLoS Pathogens, 2022)
We have recently shown that the replication of rhinovirus, poliovirus and foot-and-mouth disease virus requires the co-translational N-myristoylation of viral proteins by human host cell N-myristoyltransferases (NMTs), and is inhibited by treatment with IMP-1088, an ultrapotent small molecule NMT inhibitor. Here, we examine the importance of N-myristoylation during vaccinia virus (VACV) infection in primate cells and demonstrate the anti-poxviral effects of IMP-1088. N-myristoylated proteins from VACV and the host were metabolically labelled with myristic acid alkyne during infection using quantitative chemical proteomics. We identified VACV proteins A16, G9 and L1 to be N-myristoylated. Treatment with NMT inhibitor IMP-1088 potently abrogated VACV infection, while VACV gene expression, DNA replication, morphogenesis and EV formation remained unaffected. Importantly, we observed that loss of N-myristoylation resulted in greatly reduced infectivity of assembled mature virus particles, characterized by significantly reduced host cell entry and a decline in membrane fusion activity of progeny virus. While the N-myristoylation of VACV entry proteins L1, A16 and G9 was inhibited by IMP-1088, mutational and genetic studies demonstrated that the N-myristoylation of L1 was the most critical for VACV entry. Given the significant genetic identity between VACV, monkeypox virus and variola virus L1 homologs, our data provides a basis for further investigating the role of N-myristoylation in poxviral infections as well as the potential of selective NMT inhibitors like IMP-1088 as broad-spectrum poxvirus inhibitors.